DETERMINATION OF RESTING TIME BASED ON PHYSIOLOGY WORKLOAD MEASUREMENT TO IMPROVE PRODUCTION OPERATOR PERFORMANCE (CASE STUDY IN PT. PLASTIC AND CHEMICAL INDO TPC) (International Journal of Psychosocial Rehabilitation, 2020)
PT. TPC Indo Plastic and Chemicals is one of the PVC resin companies located in Gresik Regency. Machine used PT. TPC, especially in packaging (Packing) is a semi-automatic machine, so it still needs manpower to process the workmanship. The process of working in the packing division is divided into three phases, namely Feeding, Sewing, and Stuffing. The three processes have a target of 330,000 tonnes per day. High target companies are not always able to be achieved because according to the data that research there is a decline in production of the first 2 hours, it can initially meet the target of 30.2% decreased to 16.7% in the last 2 hours. It is the goal of this research to assess the physical workload category of workers through a physiological approach. The method used is the physiologic factor of the worker in the Cardiovascular Load (CVL) measurement obtained from the measurement of pulse rate with pulse and oxygen consumption, and energy consumption. In addition, the study also conducted interviews and disseminated workload questionnaire. As a result, workers experience a working fatigue rate of 66% of the total operator, requiring a more than 23.05 minutes increase of downtime